PENCIPTAAN MANUSIA BERDASARKAN KEJADIAN 1:26-28 SEBAGAI EVALUASI TERHADAP PERILAKU TRANSGENDER DALAM PERSEPSI UMAT KRISTEN - Dorce Sondopen; Grace Anggraini Gloria; Horas Fransiskus Gultom (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2023)
Abstract: This article describes the study of human creation as an evaluation of transgender behavior in the perception of Christians. So much exciting and controversial news has appeared on social media and is circulating among churches and the community. This news is being debated especially among Christians, giving rise to pro and contra thoughts on the existence of transgender people in general. Where transgender behavior is indeed a form of deviation from social norms. This study uses a qualitative descriptive method by explaining the terms used in the title of the article, where literature and journals are the main objects in obtaining information as descriptive data in this study. The purpose of this article is to answer some of the following questions: What is meant by the creation of humans based on Genesis 1:26-28? How is transgender behavior seen from the perception of Christians? How is the creation of humans based on Genesis 1:26-28 as an evaluation of transgender behavior from the perception of Christians? Starting from the theoretical reference, the important points of the research results in this study are: (1) The creation of humans based on the context of events 1:26-28 aims to relate to other creations and also to fellow humans where God wants humans to multiply and multiply to fulfill earth. (2) Transgender behavior in terms of the perception of Christians is behavior that is contrary to the principles and teachings of the Bible, which arises as a result of sin and must be prohibited because it deviates from social norms (3) According to the context of Genesis 1:26-28, humans are created according to image and likeness of God. The Bible teaches that every human being must be grateful for every gender that God has given him by not trying to change or carry out sexual deviations that contaminate the body such as transgender. The human body is God's temple which must be cared for and cared for to glorify God. Transgender perpetrators, on the one hand, are sinful according to the Bible, but on the other hand, they still have to be loved and served with God's love so that they are aware, repent and return to the right path, with normal behavior and glorify God.